Users’ satisfaction level on nursing facilities in shopping malls in Penang / Farizah Mohammad Nor and Edelin Hussein - Mohammad Nor, Farizah; Hussein, Edelin (2018)
Today, the number of people going to shopping complex has increased. Nursing facilities is one of the many types of facilities that should be provided in shopping malls. The aim for this research is to study customers’ satisfaction level towards baby care facilities provided in shopping malls in Penang. The research looks into the availability of babycare room facilities provided in shopping complex, to determine the level of customers’ satisfaction when using the facilities and to suggest the ways to improve the baby care room facilities provided there. The scope of this research is focused at Queensbay Mall, Gurney Paragon Mall and First Avenue Mall. A questionnaire was used to achieve the objectives which was distributed to the users of the baby care room in the shopping malls. The data were analyzed by using SPSS software version 23. Result relating to the availability of facilities in baby care rooms indicated that all the case study buildings are designed with the baby care room facilities. The outcome from the survey indicate designed have high satisfaction on cleanliness as well as comfort and facilities category while a moderate satisfaction in the aspect of security, direction and location. In the aspect of security, direction and location for Gurney Paragon, most users showed high satisfaction while First Avenue showed a moderate satisfaction. Morover, on suggestions to improve baby care facilities, Gurney Paragon has the highest ranking on Cleanliness, comfort, direction as well as location while First Avenue Showed security and facilities categories as the highest rank